Pengabdian sebagai Nilai Pendidikan Sosial Masyarakat dalam Novel Tenun Biru Karya Ugi Agustuno J. Suatu Tinjauan Sosiologi Sastra - Umi Khomsiyatun (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2016)
Abstract: The social value is something that is embraced by the people in the social life that can affect one’s actions to behave and act. One form of social value is devotion. Devotion is a process or way or the act served or are devoted to doing something good done by humans to other humans with sincerity. Devotion becomes a form of social-education value in public in real life. In relation to the novel that has been analyzed, there are some points of the forms of devotion found. Forms of devotion to human being. Keywords: Value, Devotion, Community.